Synchrotron X-ray diffraction and scanning electron microscopy to understand enamel affected by metabolic disorder mucopolysaccharidosis. (April 2016) - Khan, Malik Arshman; Addison, Owen; James, Alison; Hendriksz, Christian J.; Al-Jawad, Maisoon
Highlights: Mucopolysaccharidosis (MPS) is an inherited metabolic disorder. Synchrotron X-ray diffraction and scanning electron microscopy have been used to study normal dental enamel and dental enamel affected by mucopolysaccharidosis (MPS). Presence of a partially calcified layer between the enamel and dentine at the EDJ (Enamel Dentine Junction) in a MPS affected tooth can cause the tooth to become weak and fracture whereas scalloping of EDJ seen in a normal tooth allows the tooth structure to become more stable and resist fracture. Abstract: Mucopolysaccharidosis (MPS) is an inherited metabolic disorder that can affect the tooth structure leading to defects. Synchrotron X-ray diffraction being a state of the art technique has been used to determine the enamel crystallite orientation in deciduous enamel affected by Mucopolysaccharidosis Type I and Mucopolysaccharidosis Type IVA and comparing these with that of healthy deciduous enamel. Using this technique it was observed that there is a loss of texture in deciduous enamel affected by Mucopolysaccharidosis Type I and Mucopolysaccharidosis Type IVA when compared to the healthy deciduous enamel. Generally it was observed that the incisal surface of the deciduous teeth possessed a higher texture or preferred orientation of enamel crystallites and on progression towards the cervical region there was a decrease in the texture or preferred orientation of enamel crystallites. Scanning electron microscopy showed that the presence of a poorly calcified layer between the enamel and dentine at the enamel–dentine junction (EDJ) in MPS affected samples was likely to be responsible for rendering the tooth structure weak and prone to fracture as is often the case in MPS affected deciduous enamel.